2018
DOI: 10.1177/2515690x18801577
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Hepatocurative Effect of Aqueous Fraction of Tapinanthus bangwensis Against Paracetamol-Induced Hepatotoxicity

Abstract: Medicinal plants over time have proven to have potential to manage a huge number of diseases and disorders and thus have become a great source of pharmaceutical drugs. One of such plants is Tapinanthus bangwensis (African mistletoe). It is a semiparasitic and epiphytic plant growing on citrus tree, obtaining its food photosynthetically while its nutrient and water is got from the host plant. The aim of this study was to determine the cytotoxicological and hepatocurative effect of aqueous fraction of T bangwens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The determination of higher moisture content in this study indicated the more probability of microbial attack and enzymatic hydrolysis of the plant materials [44,[45][46][47]. The higher extraction yield of mistletoes using water and methanol in this study might be associated to the higher polarity of the extraction materials, the particle size of the raw materials, the solvent-to-solid ration, the extraction temperature and the extraction duration [48][49].…”
Section: Discussionmentioning
confidence: 83%
“…The determination of higher moisture content in this study indicated the more probability of microbial attack and enzymatic hydrolysis of the plant materials [44,[45][46][47]. The higher extraction yield of mistletoes using water and methanol in this study might be associated to the higher polarity of the extraction materials, the particle size of the raw materials, the solvent-to-solid ration, the extraction temperature and the extraction duration [48][49].…”
Section: Discussionmentioning
confidence: 83%
“…In contrast deficiency of these trace elements especially zinc and copper cause oxidative stress and damage to biological molecules and membranes (McDowell et al, 2007). Therefore the hepatocurative effect observed in this study could be due to the presence of copper and zinc and/or strong antioxidant activity exhibited by crude methanol extracts/fractions of the plants which may be attributed to the presence of phytochemical compounds inherent in them (Ihegboro et al, 2018). The increased levels of triglycerides, cholesterol and low density lipoprotein as shown in table 5 may be due to defective metabolism of phospholipids, increased biosynthesis from acetate, increased fatty acid esterification, inhibition of fatty acid betaoxidation or decreased excretion of cellular lipids (Weber et al, 2003;Fernandez and West, 2005;).…”
Section: Effects On Liver Histologymentioning
confidence: 83%
“…The English acronyms for the plant are "all heal tree, "bird lime" or "tree of life" while various ethnic groups in Nigeria such as Hausa call it Kauci (Kanchi), Yoruba-, Afomo onisana and Igbo-Awurusie (or Apari). Its ethno-medicinal benefits include anti-inflammatory, anti-microbial, anticancer, hypotensive and hypoglycemic effects (Ihegboro et al, 2018). Moringa oleifera is referred to as miracle trees and belong to the Moringaceae family.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the host constituents may be exchanged with the mistletoes and vice versa, therefore enhancing their medicinal properties. In fact, according to traditional medicine practices, mistletoes growing on guava, kola nuts and citrus are mostly used for the treatment of diseases such as cancer, hypertension, nervousness and insomnia, while those growing on cocoa are specifically efficient against hyperglycaemia [3]. African mistletoes are known as "all-purpose plants" because they were beneficial in folklore medicine as a remedy for many health problems [4].…”
Section: Introductionmentioning
confidence: 99%